2016
DOI: 10.1111/imj.13007
|View full text |Cite
|
Sign up to set email alerts
|

Weight satisfaction, management strategies and health beliefs in knee osteoarthritis patients attending an outpatient clinic

Abstract: Despite desiring and attempting to lose weight, obese people with symptomatic knee OA more commonly reported weight gain. Overweight and obese participants attributed weight gain to non-modifiable factors but believed physical activity is more important than dietary change in weight management. Thus, education regarding the importance of diet as compared with non-modifiable factors and physical activity may improve weight management in obese people with knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…We also found that a barrier to weight control was difficulty controlling appetite, echoing a report that that obese knee OA patients in the UK perceived overconsuming food as a barrier to healthy eating [13]. In addition, our participants described weight loss as difficult to achieve and maintain, as reported for older adults with knee OA in Australia [10]. Another barrier to weight control described by our participants was that not eating caused discomfort, which might be due to low blood sugar.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We also found that a barrier to weight control was difficulty controlling appetite, echoing a report that that obese knee OA patients in the UK perceived overconsuming food as a barrier to healthy eating [13]. In addition, our participants described weight loss as difficult to achieve and maintain, as reported for older adults with knee OA in Australia [10]. Another barrier to weight control described by our participants was that not eating caused discomfort, which might be due to low blood sugar.…”
Section: Discussionsupporting
confidence: 76%
“…However, such people find weight loss difficult to achieve and maintain [ 10 ]. Few studies have addressed the barriers to weight control among patients with knee OA [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, no studies identified the patient perceived need for weight loss services. It has been shown that patients with OA are aware of the need for weight loss 61 and desire information regarding lifestyle modification that may improve their OA symptoms 42 , however, they make few effective efforts to lose weight 11,61 . This need was not captured by this review.…”
Section: Discussionmentioning
confidence: 99%
“…Although this research contained no direct patient or public involvement, the research question was informed by work with a consumer organisation identifying patient needs in musculoskeletal disease36 and an audit of consumer with knee and hip pain to identify health beliefs in weight management 37…”
Section: Methodsmentioning
confidence: 99%